A REVISED PALAEOGENE LITHOSTRATIGRAPHIC FRAMEWORK FOR THE NORTHERN SWISS JURA AND THE SOUTHERN UPPER RHINE GRABEN AND ITS RELATIONSHIP TO THE NORTH ALPINE FORELAND BASIN - CLAUDIUS PIRKENSEER; GAËTAN RAUBER; STÉPHANE ROUSSÉ (Rivista Italiana di Paleontologia e Stratigrafia, 2018)
The Palaeogene deposits in the Swiss Molasse Basin, the intermediate Swiss Jura and the adjacent southern Upper Rhine Graben represent an excellent case study for interbasinal sedimentary and palaeogeographic relationships. The topographic and geologic complexity of the area led to an accumulation of local stratigraphic terms during nearly 200 years of research activity, necessitating a simplification of the lithostratigraphic framework. Additionally, the extension of the investigated area over two historically shifting language areas and the absence of a standardised supraregional lithostratigraphy adds to complexity of the situation.